AB0829 2012 American Guidelines for The Management of Gout as Seen by Family Doctors in France. (15th July 2016) - Mourgues, C.; Soubrier, M.; Pereira, B.; Vorilhon, P.; Mathieu, S.
Abstract : Background: Gout is a common and potentially serious rheumatological disease. Its management in France remains inadequate, with target serum uric acid (SUA) levels being reached in 20% of cases. American guidelines for the management of gout were released in 2012. Objectives: Our aim was to assess whether family doctors in Auvergne, France, agreed with the 14 recommendations for managing gout by mailing them a questionnaire. Methods: An anonymous questionnaire was mailed to all the family doctors in our region in November 2014. Results: The response rate was 40% (n=505/1263). Of the 505 family doctor respondents (FDRs), 60% had been in practice for more than 20 years. Some 56.2% were in practice in rural areas, and 53.6% followed on average 5 to 20 gout patients. Management of acute gout: 90.7% of FDRs agreed with pharmacological management within 24 hours of the attack; 95% of FDRs agreed with using colchicine, 72% short-course nonsteroidal anti-inflammatory drugs, and 16.6% corticosteroids; 81% approved of continuing hypouricemic therapy during the attack. Management of chronic gout: 61.6% agreed with not treating asymptomatic hyperuricemia. Allopurinol or febuxostat are used as the first-line therapies according to 88.7%. Half of respondents lowered target SUA when gout was tophaceous. Conclusions: The guidelines generally met with the approval of family doctors in Auvergne (72% agreement). They were also confirmed on a European level in 2014. Their use should be disseminated with, however, some additional clarifications, particularly for the management of chronic gout. Disclosure of Interest: None declared